Morphology, taxonomy and genetics of tropical diatom pseudo-nitzschia species (bacillariophyceae) in Malaysian waters - Lim, Hong Chang (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Pseudo-nitzschia is a marine pennate diatom known to be responsible for Amnesic shellfish poisoning (ASP) due to domoic acid (DA) production, a type of neurotoxin. Field studies were conducted from Malaysian Borneo and Straits of Malacca, Peninsular Malaysia to determine the species occurrence, and distribution of brackish to marine diatom Pseudo-nitzschia. A total of four species were identified based on a combination of distinct morphological characteristics and supporting molecular evidence: P. brasiliana, P. dolorosa, P. micropora, and P. pungens. One morphotypes from Sarawak; however showed significant morphological distinction from the known species while similar to that of P. caciantha. Most notably this morphotypes possessed a characteristic pore arrangement in the poroids with the fine pores arranged in circular close to the margin of the poroid hymen. The large subunit (LSU) rDNA of this morphotype and closely related P. caciantha Lundholm, Moestrup & Hasle, showed 2.7% genetic divergence. Phylogenetic analyses strongly supported the monophyly of the morphotype. Based upon these supporting data it is here described as a new species, Pseudo-nitzschia circumpora sp. nov. Molecular signatures for all species were established based on structural comparisons of the second internal transcribed spacer (ITS2) rRNA transcripts. In addition, another three new species were proposed from cultures obtained from the Straits of Malacca based on morphological data combined with molecular evidences; viz. P. batesiana sp. nov., P. lundholmiae sp. nov., and P. fukuyoi sp. nov. The three new species closely resemble species in the P. pseudodelicatissima complex sensu lato. Morphologically, P. batesiana differs from other species in the complex (i.e. P. fukuyoi) by having a smaller part of cell overlapping in the chain, whereas P. lundholmiae differs by having fewer poroid sectors and P. fukuyoi by having a distinct type of poroid sectors. Nucleotide sequences of the LSU rDNA of the three new species reveal significant nucleotide sequence divergence from each other and from the other species in the P. pseudodelicatissima complex s.l. The three species show 2-3 compensatory base changes (CBCs) in their ITS2 transcripts when compared to closely related species. The three species are phylogenetically closely related to species in the P. pseudodelicatissima complex, with P. batesiana appearing as a sister taxon to P. circumpora, P. caciantha and P. subpacifica; while P. lundholmiae and P. fukuyoi are more closely related to P. pseudodelicatissima and P. cuspidata. The effectiveness of using ribosomal gene of LSU rDNA (domain 1-3), the whole region of ITS (ITS1- 5.8S-ITS2) and ITS2 together with structural alignment to discriminate Pseudonitzschia to species level were shown in this study. To examine the genetic diversity of Pseudo-nitzschia in Malaysia, two commonly found Pseudo-nitzschia i.e. P. brasiliana and P. pungens were selected. Hence, the genetic marker of internal transcribed spacer (ITS) of nuclear-encoded ribosomal DNA of this two species was used to clarify diversity and population structure. In P. brasiliana, high genetic homogeneity was detected (0.07-0.54%) but no clear trend on geographical localities, v phylogenetically. The low geographical patterns lead to the conclusion that there‟s no speciation although P. brasiliana from Malaysian waters was geographically isolated. Whereas in P. pungens, phylogenetic tree from Profile Neighbour Joining (PNJ) analysis revealed that there are three ITS entities (Clade I to Clade III), in which strains in clade I found to be distributed widely in Northern and Southern Hemisphere, clade II confined only to NE Pacific and clade III restricted to tropical and subtropical waters. The result also showed that there is no gene flow between P. pungens from warm tropical water and cold temperate water and the populations were genetically structured based on AMOVA (ФST=0.7495) and STRUCTURE analysis. The evolutionary diversification patterns of P. pungens were first revealed based on these analyses. Additionally, we present a phylogeographical hypothesis in which the evolutionary of P. pungens is triggered by ecological differentiation due to the closure of Central American Seaway and the global distribution is driven by thermohaline circulation. These hypotheses are consistent with the formation of Isthmus of Panama. In conclusion, high diversity Pseudo-nitzschia was documented in this study with the description of four new species. Species diversification and phylogeography of P. pungens served as a model demonstrated in this study in understanding speciation in marine diatom in particularly the potentially toxic Pseudo-nitzschia species.